Molecular characterization of guadua angustifolia kunth using rams (2012)
Guadua angustifolia Kunth is a neotropical bamboo species distributed in the Andean region of Colombia. But has a great industrial importance in the well known Colombian coffee region due its use in building, industrialization and furniture. In order to know the genetic diversity of nine superior materials of G. angustifolia previously selected by morphologic and physical characteristics(mechanic characteristics, a molecular characterization using RAMs molecular markers Gas carried out. Values of He 4 6.3; and polymorphic loci percentage of 8;.63% were obtained, indicating a high genetic diversity of the evaluated materials.